Effect of Near-Fault Pulsed Ground Motions on Seismic Response and Seismic Performance to Tunnel Structures - Xiancheng Mei; Qian Sheng; Zhen Cui (Shock and Vibration)
Seismic analysis of tunnels close to or crossing seismogenic faults is a complex problem, which is often neglected at the design stage for the lack of specific codes or guidelines and also because underground structures are considered less vulnerable than that of the corresponding above-ground facilities. Near-fault ground motions are generally assumed to providing more powerful energy to tunnel structures. Therefore, a recently developed velocity pulse equivalent model is proposed to synthesize the artificial near-fault pulsed ground motion for the seismic response behavior of the tunnel structure. A newly proposed nonlinear dynamic time history methodology, the incremental dynamic analysis method, is introduced into the analysis of seismic performance and fragility for tunnel structures. This study takes the Zheduoshan tunnel as a case study to illustrate the effects of velocity pulse on the seismic response behavior and seismic performance. The applicability of different seismic intensity measures is preliminarily discussed, and the vulnerability of the tunnel structure at different characteristic locations is analyzed. Afterward, the seismic vulnerability probabilities of the tunnel structure under the action of the near-fault pulsed ground motions and the far-field ground motions are presented, and then, the failure probabilities of the tunnel structure under the three-level support requirements are obtained. Research results provide an objective assessment of the velocity pulse effects and acts as a reference for the likely seismic damage assessment of tunnel structures.